Immune resistance and tolerance strategies in malaria vector and non-vector mosquitoes - Habtewold,T; Groom,Z; Christophides,G (Parasites & Vectors, 2017)
BackgroundThe Anopheles gambiae complex consists of species that vary greatly in their capacity to transmit malaria. The mosquito immune system has been identified as a key factor that can influence whether Plasmodium infection establishes within the mosquito vector. This study was designed to investigate the immune responses of An. coluzzii, An. arabiensis and An. quadriannulatus mosquitoes. The first two mosquito species are major vectors of malaria in sub-Saharan Africa, while the third is thought to be a non-vector.MethodsAll three mosquito species were reared in mixed cultures. Their capacity to eliminate P. berghei and regulate midgut bacteria was examined.ResultsOur results revealed large differences in mosquito resistance to P. berghei. In all three mosquito species, immune reactions involving the complement system were triggered when the number of parasites that mosquitoes were challenged with exceeded a certain level, i.e. immune tolerance threshold. This threshold was markedly lower in An. quadriannulatus compared to An. coluzzii and An. arabiensis. We also demonstrated that the level of immune tolerance to P. berghei infection in the haemolymph is inversely correlated with the level of immune tolerance to microbiota observed in the midgut lumen after a blood meal. The malaria non-vector mosquito species, An. quadriannulatus was shown to have a much higher level of tolerance to microbiota in the midgut than An. coluzzii.ConclusionsWe propose a model whereby an increased tolerance to microbiota in the mosquito midgut results in lower tolerance to Plasmodium infection. In this model, malaria non-vector mosquito species are expected to have increased immune resistance in the haemocoel, possibly due to complement priming by microbiota elicitors. We propose that this strategy is employed by the malaria non-vector mosquito, An. quadriannulatus, while An. coluzzii has reduced tolerance to bacterial infection in the midgut and consequently reduced immune resistan